Survey Study: Based On Current Trends of People Regarding Self-Medication - Trivedi, Naitik; Patel, Himaxi; Patel, Janvi; Pavagadhi, Nidhi; Trivedi, Upama (Asian Journal of Pharmaceutical Research and Development, 2021)
This study was performed at Sai Druggist and Chemist Shop, Anand, Gujarat. We have included total number of 30 patients in our study to know current trends of people regarding self-medication in the region of anand district. Based on this study we have observed that out of total 30 patients 12 had taken the drug via prescription and 18 had taken the self-medication. We have performed the study on both the sex groups male and female and we observed that 10 male and 8 female had taken the self-medication, and 7 male and 5 female had taken the prescribed medication. Out of total patient 10 patient taken the self-medication by their own experience, 7 patients taken self-medication suggested by friend/family member and 1 patient taken self-medication suggested by the media/advertisement.